Peningkatan Kapasitas Sumberdaya Manusia Pengelola Desa Wisata Di Desa Mranggen Kecamatan Jatinom Kabupaten Klaten Jawa Tengan - Nugroho, Agung Satriyo; Putri, Bintang Cahya Rokhmana; Sekar, Kinanthi Sukmaning (Journal of Dedicators Community, 2025)
Mranggen Village is a village on the slopes of Mount Merapi which has potential natural resources including springs for agricultural areas in Klaten Regency, Central Java. This village has become a partner village of the Department of Development Geography,  Faculty of Geography UGM since 2020. The big theme of regional development study in this village is Tourism Village. In the first and second years, the design of the tourist village has been successfully compiled, with one of the outputs being the stipulation of Mranggen Village as a tourist village through the Klaten Regent's Decree in 2021. In this third year, assistance for the development of Mranggen Village is carried out with efforts to increase the capacity of human resource managers tourist village. Human resource capacity building starts white developing a participatory tourism village management system. after that, training related to materials to support the implementation can be carried out. The training is carried out using a comparative study scheme with developed tourist villages. The result of this activity is a tourism village management system along with an increase in human resource capacity which is assessed from the assessment before and after the implementation of the training